To solve the system of equations using substitution, we have:
- Equation 1: \( y = x^2 - 4x + 8 \)
- Equation 2: \( y = 3x - 4 \)
We can set the two equations equal to each other since both equal \( y \):
\[ x^2 - 4x + 8 = 3x - 4 \]
Now, let's rearrange it to form a standard quadratic equation:
\[ x^2 - 4x - 3x + 8 + 4 = 0 \] \[ x^2 - 7x + 12 = 0 \]
Now, factor the quadratic:
\[ (x - 3)(x - 4) = 0 \]
Setting each factor to zero gives us the values for \( x \):
- \( x - 3 = 0 \) → \( x = 3 \)
- \( x - 4 = 0 \) → \( x = 4 \)
Next, we can find the corresponding \( y \) values by substituting \( x \) back into either of the original equations. We'll use the second equation for simplicity:
For \( x = 3 \): \[ y = 3(3) - 4 = 9 - 4 = 5 \] So one solution is \( (3, 5) \).
For \( x = 4 \): \[ y = 3(4) - 4 = 12 - 4 = 8 \] So the second solution is \( (4, 8) \).
Thus, the solutions to the system are:
- \( (3, 5) \)
- \( (4, 8) \)
The correct response is:
(4,8) and (3,5)
or in the requested format:
left parenthesis 4 comma 8 right parenthesis and left parenthesis 3 comma 5 right parenthesis.